2020
DOI: 10.1111/jcmm.15762
|View full text |Cite
|
Sign up to set email alerts
|

A lncRNA prognostic signature associated with immune infiltration and tumour mutation burden in breast cancer

Abstract: Over the last decade, with the rapid development in the depth and quality of transcriptome sequencing, long non-coding RNAs (ln-cRNAs) longer than 200 nucleotides in length, which were once thought to be biological noise, were discovered in abundance. Research investigating lncRNAs has progressed notably in every field of medical research. 1 Accumulating evidence has demonstrated that lncRNAs are involved in diverse cellular processes, including transcription initiation, chromatin modification and transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 42 publications
1
83
0
Order By: Relevance
“…For example, Luan et al [34] knocked down the lncRNA NPPA-AS1 in human normal cervical epithelial cells (H8 cells) and human cervical cancer cells (C33A, CaSki, HeLa, and SiHa cells) and showed that this lncRNA impaired cell proliferation and migration. Moreover, lncRNAs are known to participate in the progression of lung cancer, breast cancer, and cervical cancer [34][35][36][37]. Additionally, various lncRNAs can affect disease occurrence and outcomes through multiple molecular pathways.…”
Section: Types and Mechanisms Of Lncrnas In Osteogenic Differentiationmentioning
confidence: 99%
“…For example, Luan et al [34] knocked down the lncRNA NPPA-AS1 in human normal cervical epithelial cells (H8 cells) and human cervical cancer cells (C33A, CaSki, HeLa, and SiHa cells) and showed that this lncRNA impaired cell proliferation and migration. Moreover, lncRNAs are known to participate in the progression of lung cancer, breast cancer, and cervical cancer [34][35][36][37]. Additionally, various lncRNAs can affect disease occurrence and outcomes through multiple molecular pathways.…”
Section: Types and Mechanisms Of Lncrnas In Osteogenic Differentiationmentioning
confidence: 99%
“…LncRNAs has recently been shown to be closely related to the occurrence and development of tumors and abnormal expression of some lncrnas can be prognostic markers in tumor patients [30][31][32][33][34][35] . With the development of research, people realize that lncrNA also plays an important role in Tumor mutational burden (TMB) [36]. For example, lncRNA DDSR1 participates in DNA damage Response (DDR), and DDR variation will lead to TMB variation [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on the rst mock exam results of multivariate Cox proportional hazards analysis, the nomogram was established using the R package "RMS" to predict the total recurrence rate of 1, 3, 5 years. This model was helpful for us to calculate the prognosis risk of a single patient by the point at which each risk factor was related 26 .…”
Section: Establishment Of Prognosis Modelmentioning
confidence: 99%